2020
DOI: 10.1590/1983-1447.2020.20190290
|View full text |Cite
|
Sign up to set email alerts
|

Association between social support and adherence to anti-retroviral treatment in people living with HIV

Abstract: Objective: To investigate the association between social support, adherence to HIV anti-retroviral therapy, and clinical and sociodemographic factors. Method: A cross-sectional study conducted from July 2016 to August 2018 in a specialized outpatient clinic in southern Brazil. Individual interviews were conducted for the application of the following instruments: Questionnaire for the Evaluation of Adherence to Anti-retroviral Treatment (CEAT-HIV) and Social Support Scale for People Living with HIV/AIDS. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
3
12
0
2
Order By: Relevance
“…This finding agrees with the literature from Ethiopia, Uganda, Kenya, Zimbabwe, and Mozambique, about adults and youth with HIV where again family and friends provided among others, food, money, encouragement and love, and reminders that helped them overcome multiple barriers to ART adherence. 27,67,71,72,75 Consistent with findings from the USA and South Africa among adult and older patients (50+) with HIV [47,68], this study also found that bonding networks, particularly family members, were also key in protecting some of YALWH against stigma and also helped them cope with HIV.…”
Section: Perceived Roles Of Social Networksupporting
confidence: 85%
See 2 more Smart Citations
“…This finding agrees with the literature from Ethiopia, Uganda, Kenya, Zimbabwe, and Mozambique, about adults and youth with HIV where again family and friends provided among others, food, money, encouragement and love, and reminders that helped them overcome multiple barriers to ART adherence. 27,67,71,72,75 Consistent with findings from the USA and South Africa among adult and older patients (50+) with HIV [47,68], this study also found that bonding networks, particularly family members, were also key in protecting some of YALWH against stigma and also helped them cope with HIV.…”
Section: Perceived Roles Of Social Networksupporting
confidence: 85%
“…Our findings are similar to those of other studies conducted in Brazil, Zambia, and Kenya among adults (>18 years) with HIV, where again friends and family and not neighbors were the dominant forms of social networks. 27,71,73,75 However, in the USA, social networks of older adults with HIV (50+yrs) were mostly composed of smaller (fragile) networks of older friends (often living with HIV), whom they relied on than family members for support. [43][44][45][46] Previous literature on HIV indicates that women were more likely to care for PLWH than men.…”
Section: Social Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo evidenciou que há correlação positiva entre suporte emocional e situações que mostram falta de adesão antecedente, e que a adesão e o suporte social se correlacionam positivamente com a comunicação entre o médico e o paciente (Oliveira et al, 2020). Isso indica que, apesar de o tratamento atual ser de primeira linha, a consciência construída culturalmente sobre a infecção prejudica a EAE e a confiança em si mesmo para executar atividades benéficas em relação ao tratamento.…”
Section: Discussionunclassified
“…Studies have revealed spouses or partners, family members, in or out of the family environment, and friends as the main sources of social support for people living with HIV and AIDS (10)(11)(12) . However, despite the scarcer offer of support, colleagues, neighbors, bosses at work, and the health team are also referred to as sources of support (10)(11)13) .…”
Section: Introductionmentioning
confidence: 99%